History and current status of biological tests in Russia - M. S. Ryabtseva; T. A. Batuashvili; G. A. Sapozhnikova; N. P. Neugodova; Yu. V. Olefir; V. A. Merkulov (Регуляторные исследования и экспертиза лекарственных средств, 2018)
«Pyrogenicity» and «Abnormal Toxicity» are considered to be among most problematic pharmacopoeia monographs in the current editions of the leading world pharmacopoeias, the reasonability of which is not obvious to all experts. The authors analyze the reasons for the introduction and history of the elaboration of biological methods for drug quality control, as well as major prospects for their further development in Russia.